A systematic review of surgical intervention in the treatment of hamstring tendon ruptures: current evidence on the impact on patient outcomes. (31st December 2022) - Jokela, Aleksi; Stenroos, Antti; Kosola, Jussi; Valle, Xavier; Lempainen, Lasse
Abstract: Hamstring injuries are among the most common muscle injuries. They have been reported in many different sports, such as running, soccer, track and field, rugby, and waterskiing. However, they are also present among the general population. Most hamstring injuries are mild strains, but also moderate and severe injuries occur. Hamstring injuries usually occur in rapid movements involving eccentric demands of the posterior thigh. Sprinting has been found to mainly affect the isolated proximal biceps femoris, whereas stretching-type injuries most often involve an isolated proximal injury of the semimembranosus muscle. The main cause of severe 2- or 3-tendon avulsion is a rapid forceful hip flexion with the ipsilateral knee extended. Most hamstring injuries are treated non-surgically with good results. However, there are also clear indications for surgical treatment, such as severe 2- or 3-tendon avulsions. In athletes, more aggressive recommendations concerning surgical treatment can be found. For a professional athlete, a proximal isolated tendon avulsion with clear retraction should be treated operatively regardless of the injured tendon. Surgical treatment has been found to have good results in severe injuries, especially if the avulsion injury is repaired in acute phase. In chronic hamstring injuries and recurring ruptures, the anatomical apposition of the retracted muscles is more difficult to be achieved. This review article analyses the outcomes of surgical treatment of hamstring ruptures. The present study confirms the previous knowledge that surgical treatment of hamstring tendon injuries causes good results with high satisfaction rates, both in complete and partial avulsions. Early surgical repair leads to better functional results with lower complication rates, especially in complete avulsions. KEY MESSAGEs: Surgical treatment of hamstring tendon ruptures leads to high satisfaction and return to sport rates. Both complete and partial hamstring tendon ruptures have better results after acute surgical repair, when compared to cases treated surgically later. Athletes with hamstring tendon ruptures should be treated more aggressively with operative methods.